Cost Budget Variance - Seto Sulaksono Adi Wibowo; Dwi Amelia Putri; Yosi Handayani (Politeknik Negeri Batam, 2021)
The research was conducted at the Scanner Engineering Department of PT Epson Batam. The topic is written about budget management for repair and maintenance (die & mold) costs with the aim of knowing how to minimize the variance between budgeted costs and their realization. Data collection methods used in this study were interviews, observation, and documentation, and descriptive and quantitative methods were used for data analysis. The existing budgeting system in the Scanner Engineering Department has been carried out correctly and effectively met the objectives, but overall during the 2018 fiscal year there were budget inefficiencies. Based on observations, it is known that from the budget made there are still differences (favorable variance and unfavorable variance). Where the difference arises due to unexpected costs for damaged equipment, the difference between the scheduled repair time (service) and the reality, as well as delays in sending invoices or debit notes.